Penerapan Internet Of Things dan You Only Look One Pada Sistem Keran Air Wudhu Pintar Sebagai Edukasi Siswa - Laksana, Fatih Dwi; Fitri, Zahratul; Suwanda, Rizki (Jurnal Algoritma, 2025)
This study aims to develop a smart wudhu water tap system based on the Internet of Things (IoT) as an interactive educational medium for students. The system is equipped with object detection sensors, voice guidance, and the YOLOv8 algorithm to detect and classify wudu movements in real-time. Accuracy evaluation was performed using the Fuzzy Takagi-Sugeno-Kang (TSK) method, which categorizes the results into three levels: “Low,” “Medium,” and “High.” Test results show excellent detection performance, with an average mAP50 value of 0.993, mAP50-90 of 0.746, recall of 0.998, and defuzzification results in the “High” category. This system is effective in providing educational feedback and supporting technology-based wudhu learning. In the future, this system has the potential to be implemented in schools on a larger scale and developed to improve its accuracy and functionality.